Endemism in host–parasite interactions among island populations of an endangered species. Issue 4 (10th January 2013) - Harris, Nyeema C.; Coonan, Timothy J.; King, Julie L.; Dunn, Robert R.; Fitzpatrick, Matt
Abstract Aim Implicit in conserving interactions is the idea that species behave differently throughout their range, resulting in functionally dissimilar populations of the same species. Host–parasite interactions are a useful system to explore the pervasiveness of these ecological phenotypes. Here, we investigated whether the role of an endangered, endemic species to provide habitat for ectoparasites varies throughout the geographic distribution of the host. Location Channel Islands, California. Methods We captured island foxes (Urocyon littoralis sp.) from three populations: Santa Catalina (n = 72), Santa Rosa (n = 79) and San Miguel (n = 83). We compared the extent to which variation in parasite attributes were due to differences among individuals or populations. As a measure of the latter, we used discriminant function analysis to determine whether individuals from the same population 'cluster' together when comparing patterns of intensity in various ectoparasites. Results We identified eight ectoparasite species that included at least six new parasite records for island foxes. We found that ectoparasite attributes including diversity and intensity varied among host populations. More importantly, we show that knowing the parasite composition of the host can identify its population of origin, due to unique host–parasite interactions. Overall, we correctly 'assigned' 72% of island foxes to their actual, respective populations, although there were inconsistencies among populations. Main conclusions If foxes generally have the same parasite assemblage regardless of their respective populations, then conservation of a single population likely maintains all necessary species interactions and discriminate function analysis is uninformative in discerning population assignments of individuals. Our findings highlight the importance of conserving populations to maintain endemic interactions and caution against extrapolating the ecology (i.e. known species associations) of a species to other locations within their range.